Adsorption and Interfacial Properties of the Cationic Gemini Surfactant of Ethanediyl-α,β-Bis(Cetyldimethylammonium Bromide) - Wen-Sheng Liao; Zhi-Chu Bi (Adsorption Science & Technology)
The cationic gemini surfactant ethanediyl-α,β-bis(cetyldimethylammonium bromide (16-2-16) was synthesized and characterized. Aggregation of the surfactant molecules was established by surface tension measurements and viscosity methods. Some thermodynamic parameters, such as the adsorption capacity of the surface, the molecular area associated with adsorption and the free energy of micellization, were calculated from plots of the surface tension versus the concentration. The dynamic surface and interfacial tensions were measured using the pendant drop method at the air/water surface and the dodecane/water interface. The experimental curve was close to the orientation and interaction models of the surface equations of state. In comparison to conventional cationic surfactants, 16-2-16 has a very low critical micellar concentration (cmc), a higher level of surface adsorption and a lower adsorption molecular area. Due to its unique molecular structure and size, 16-2-16 adsorbs at surfaces and interfaces, but requires a considerable amount of time to attain adsorption equilibrium.